Penerapan Manajemen Strategik pada Produsen Food And Beverages - Dian Sudiantini; Bonartdo Samuel G (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2023)
. In the era of globalization and increasingly fierce competition, business people in the F&B industry are required to continue to innovate and carry out effective strategic management in order to be able to compete and win the competition in an increasingly complex market. So in this study, it will be discussed in detail about the implementation of strategic management in F&B producers. Through this research, it is hoped that readers will be able to understand the basic concepts and principles of strategic management and how they apply to the F&B industry. This study will also discuss the factors that influence success in implementing strategic management. In this study using a qualitative approach method. A qualitative approach can be used in research on the implementation of strategic management conducted by food and beverage producers to understand the perspectives of organizational leaders on how they manage management strategies to maintain the existence of a product. Based on the research that has been done, it can be concluded that the implementation of strategic management in food and beverage producers is very important to ensure business success and sustainable growth..